Multiple Oligo assisted RNA Pulldown via Hybridization followed by Mass Spectrometry (MORPH-MS) for exploring the RNA-Protein interactions - Priyanka Pant; Regalla Kumarswamy (RNA Biology)
Understanding RNA-protein interactions is crucial for deciphering the cellular functions and molecular mechanisms of regulatory RNAs. Consequently, there is a constant need to develop innovative and cost-effective methods to uncover such interactions. We developed a simple and cost-effective technique called Multiple Oligo assisted RNA Pulldown via Hybridization (MORPH) to identify proteins interacting with a specific RNA. MORPH employs a tiling array of antisense oligos (ASOs) to efficiently capture the RNA of interest along with proteins associated with it. Unlike existing techniques that rely on multiple individually biotinylated oligos spanning the entire RNA length, MORPH stands out by utilizing a single biotinylated oligo to capture all the ASOs. To evaluate MORPH’s efficacy, we applied this technique combined with mass spectrometry to identify proteins interacting with lncRNA NEAT1, which has previously been studied using various methods. Our results demonstrate that despite being a simple and inexpensive procedure, MORPH performs on par with existing methods.Abbreviations: ASO, Antisense oligo; lncRNA, long non-coding RNA; MORPH, Multiple Oligo assisted RNA Pulldown via Hybridization